Implementation of Digital Word Wall Media Based on Local Culture in Improving Reading Literacy of Elementary School Students - Apriyani, Harita Nuzul; Nisa, Ana Fitrotun; Al Masjid, Akbar; Zulfiati, Heri Maria; Bariyyah, Insanul Qisti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study analyzes students' reading skills decline at SD Negeri 2 Rejoso based on the education quality report card for the past three years. The difficulties faced by students include information comprehension, critical thinking, and ethical development. The study aimed to improve reading literacy skills using Word Wall digital learning media integrated with local culture in Gondang Winangun. The method used was a Systematic Literature Review (SLR), which analyzed 25 journal articles from 2019 to 2024. Inclusion criteria included articles that addressed the use of digital media in reading learning, while exclusion criteria eliminated irrelevant studies or did not focus on the primary education context. The data analysis techniques used were qualitative and quantitative analysis. The review results showed that 80% of the articles analyzed reported improvement in students' reading ability after applying Word Wall media. This finding confirms the importance of developing and implementing locally relevant digital learning media to improve reading literacy among primary school students.